Optimization of Criminal Fines as a Debt to the State to Enhance Non-Tax State Revenue under Law No. 1 of 2023 as an Instrument for State Financial Recovery - Anugrah R’lalana Sebayang; Sunaryo, Sunaryo; Heni Siswanto (Tinta Emas Institute, 2025)
The paradigmatic transformation of criminal fines within Law No. 1 of 2023 (the National Criminal Code) shifts its concept from a retributive sanction to an instrument of state financial recovery through the construction of